Singing and Social Identity in Young Children - Papageorgi, Ioulia; Saunders, Jo; Himonides, Evangelos; Welch, Graham F. (Frontiers in Psychology, 2022)
A range of studies suggest that singing activities with young children can have a beneficial impact on other aspects of their development. However, there is little research examining the relationship between young children’s singing and their developing social identity. In the current study, data were captured of young children’s singing and social identity as part of a larger-scale, longitudinal evaluation of the nationwide Sing Up programme in England. Participants were 720 children aged 5-8 years old. The assessment of young children’s singing ability employed an established measure and was undertaken individually. With adult support, the children were also asked to complete a simple questionnaire that focused on selected aspects of their social identity, both in general terms and also related to singing. Key themes embraced their attitudes to singing (at home, in school and in informal settings), singer identity (emotional engagement with singing and self-concept), and perceptions of self (self-efficacy, self-esteem, social integration). Comparative data were collected from young children of a similar age outside the programme. Findings suggested that the programme had a positive impact on young children’s singing ability. Positive effects were also noted on levels of self-esteem, attitudes towards singing at home and levels of perceived social integration. The data analyses suggest that children could be identified as either ‘pupils with positive singing identity’ or ‘pupils with less positive, or still developing singing identity’. Overall, pupils with a more positive singer identity tended to report more positive attitudes toward singing at school and other settings, had higher perceived levels of self-esteem and social integration, as well as more positive evaluations of their singing ability. The research suggests that successful participation in high-quality singing activities is likely to have a positive impact on both young children’s singing ability and also aspects of self that are related to contexualised singer identity and their sense of social inclusion.